Torsional behaviour of concrete-filled circular steel tubular members under coupled compression and torsion. (December 2021) - Jia, Zhi-Lu; Shi, Yan-Li; Xian, Wei; Wang, Wen-Da
Abstract: Concrete-filled steel tubular (CFST) column may be undergone coupled compression and torsion during its service life, and therefore, six CFST specimens were tested to analyze the torsional behaviour. The failure modes, torsion moment ( T ) versus torsional angle ( θ ) relationships and torsion moment-strain curves derived from the testing results for CFST specimens under different torsion conditions were compared and analyzed. Meanwhile, the numerical model of CFST members was developed via the software ABAQUS to further analyze the torsional mechanism. Moreover, the comparison of torsional performance between CFST column and steel-reinforced concrete-filled steel tubular (SRCFST) column was conducted. The results indicated that the T - θ curve of each specimen showed slight difference in the initial stage under diverse loading conditions; however, the specimens under torsion after compression exhibited highest ultimate torsional capacity, followed by the specimens under simultaneous compression-torsion and pure torsion. The T - θ curve of SRCFST columns with I-section steel or cruciform steel was similar to that of CFST columns, but the T - θ curve of SRCFST columns increased obviously in the later stage due to the inserted steel tube. In addition, the validity of the numerical model was verified against experiment. Then, the interaction force between steel tube and concrete and the internal forces of the characteristic points of the T - θ curves under different loading conditions and axial load levels were compared to understand the stress mechanism. Finally, the proposed calculation method for torsional capacity of CFST members under coupled compression-torsion could provide a more accurate prediction.